Modified double guiding catheter 'Ping Pong' technique to treat large coronary perforation: a case report. Issue 5 (16th May 2021) - Gupta, Himanshu; Kaur, Navjyot; Sharma, Yashpaul; Lim, Soo Teik
Abstract: Background : Despite improvement in available tools and techniques, procedural complications like coronary perforation can occur during percutaneous coronary intervention (PCI). Severe proximal coronary perforations are usually caused by balloon and vessel size mismatch but can also occur with appropriately sized balloons or stents if the coronary vessel has very eccentric calcification or if there is negative remodelling of the vessel. Case summary : A 74-year-old man with a history of type II diabetes mellitus, hypertension, and chronic coronary syndrome (previous PCI 10 years before) presented with unstable angina of 2 weeks of duration. Coronary angiography revealed a patent stent in left anterior descending artery, significant disease in left circumflex artery and diffuse calcified lesion in dominant right coronary artery (RCA). During angioplasty of RCA, the patient developed severe Ellis grade III perforation, which was successfully managed with modified double guiding catheter 'Ping Pong' technique. In this technique, the already engaged 7 French (F) Amplatz Left 1 guide catheter was used to deliver the bulky covered stent in highly tortuous and calcified RCA while a second 6F guide catheter (Judkin Right) introduced through contralateral femoral access was used for introducing the balloon, which initially sealed the perforation and subsequently acted as a distal anchor to provide strong support to deliver the covered stent. Conclusion : In a case of severe coronary perforation, modified Ping Pong technique using a small-sized second guide catheter complimentary to the first guide catheter, can be used to deploy bulky covered stent.